ANALISIS PENGARUH KUALITAS TENAGA PENGAJAR DAN SISTEM APLIKASI SIMAKA TERHADAP KEPUASAAN MAHASISWA INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG DENGAN PERCEIVED USEFULNESS SEBAGAI VARIABEL INTERVENING - Dwi Bagus Sasongko; Sudjilah Sudjilah; Teguh Widodo (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to analyze the effects of lecturer quality and the SIMAKA application system on student satisfaction, with perceived usefulness as an intervening variable, among students at the Asia Malang Institute of Technology and Business.Methods: The study used a quantitative approach, employing a survey. The research sample consisted of active 3rd- and 5th-semester regular class students. The data analysis technique used Partial Least Squares (Smart PLS 3.0) to test the outer model and inner model.Results: The study indicates that lecturer quality has a positive and significant effect on perceived usefulness, and the SIMAKA application system also has a positive and significant effect on perceived usefulness. Lecturer quality and the SIMAKA application system have a positive and significant effect on student satisfaction. Perceived usefulness has a positive and significant effect on student satisfaction. Furthermore, perceived usefulness mediates the effect of lecturer quality and the SIMAKA application system on student satisfaction.Conclusion and suggestion: These findings confirm that improving lecturers’ competencies and optimizing the digital academic system simultaneously can enhance students’ perceived usefulness, which ultimately strengthens student satisfaction. Keywords: Academic Information System, Lecturer Quality, Perceived Usefulness, Smart PLS, Student Satisfaction,